The Influence of the Pinyin and Zhuyin Writing Systems on the Acquisition of Mandarin Word Forms by Native English Speakers - Hayes-Harb, Rachel; Cheng, Hui-Wen (Frontiers in Psychology, 2016)
The role of written input in second language (L2) phonological and lexical acquisition has received increased attention in recent years. Here we investigated the influence of two factors that may moderate the influence of orthography on L2 word form learning: (i) whether the writing system is shared by the native language and the L2, and (ii) if the writing system is shared, whether the relevant grapheme-phoneme correspondences are also shared. The acquisition of Mandarin via the Pinyin and Zhuyin writing systems provides an ecologically valid opportunity to explore these factors. We first asked whether there is a difference in native English speakers’ ability to learn Pinyin and Zhuyin grapheme-phoneme correspondences. In Experiment 1, native English speakers assigned to either Pinyin or Zhuyin groups were exposed to Mandarin words belonging to one of two conditions: in the ‘congruent’ condition, the Pinyin forms are possible English spellings for the auditory words (e.g., <nai> for [nai]); in the ‘incongruent’ condition, the Pinyin forms involve a familiar grapheme representing a novel phoneme (e.g., <xiu> for [ɕiou]). At test, participants were asked to indicate whether auditory and written forms matched; in the crucial trials, the written forms from training (e.g., 'xiu') were paired with possible English pronunciations of the Pinyin written forms (e.g., [ziou]). Experiment 2 was identical to Experiment 1 except that participants additionally saw pictures depicting word meanings during the exposure phase, and at test were asked to match auditory forms with the pictures. In both experiments the Zhuyin group outperformed the Pinyin group due to the Pinyin group’s difficulty with ‘incongruent’ items. A third experiment confirmed that the groups did not differ in their ability to perceptually distinguish the relevant Mandarin consonants (e.g., [ɕ]) from the foils (e.g., [z]), suggesting that the findings of Experiments 1 and 2 can be attributed to the effects of orthographic input. We thus conclude that despite the familiarity of Pinyin graphemes to native English speakers, the need to suppress native language grapheme-phoneme correspondences in favor of new ones can lead to less target-like knowledge of newly learned words’ forms than does learning Zhuyin’s entirely novel graphemes.